Learning, Thinking Patterns and their Relationship to the Skill Level of the Snake Strip in the Sport of Rhythmic Gymnastics - Abdlhusen, Hadeel Abdlelah (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to know the patterns of learning and thinking and their relationship to the level of performance of the snake bar skill in the sport of rhythmic rhythm in your sport among students of the Faculty of Physical Education and Sports Science and the research sample will be (103 students e) and the researcher used the descriptive method in the survey method and the size of learning and thinking patterns to get the results of research and stomach (Torrance et al., 1978), the researcher relied on the appropriate statistical means to discuss the achieved results and reached some conclusions, including: Showed that the research sample with learning and thinking patterns according to brain functions has different classifications according to different activities. There is an association between learning and thinking patterns and the skillful performance of the snake bar in gym sport and the rhythmic rhythm between students of the Faculty of Physical Education and Sports Science.